Sex-related functional outcome after periacetabular osteotomy in mild to severe hip dysplasia - Maximilian Fischer; Lars Nonnenmacher; Andre Hofer; Alexander Zimmerer; Andreas Nitsch; Rico Großjohann; Sabrina Erdmann; Georgi I. Wassilew (Bone & Joint Open)
Aims: Periacetabular osteotomy (PAO) is well established for acetabular reorientation and has shown successful improvement in patient-reported outcome measures (PROMs). Nevertheless, studies focusing on postoperative outcomes related to patient individual factors are still underrepresented. Therefore, this study aimed to analyze the functional outcome and activity level in relation to patient sex with a minimum follow-up of two years after PAO for mild to severe hip dysplasia. Methods: A single-centre study was conducted, enrolling patients undergoing PAO and completing a preoperative and postoperative radiological and clinical outcome assessment. The PROMs were assessed using the modified Harris Hip Score (mHHS), the Hip disability and Osteoarthritis Outcome Score (HOOS) with the subscales for pain, sport, activities of daily living (ADL), and quality of life (QoL), and the University of California, Los Angeles (UCLA) activity score. Kendall’s tau were calculated for correlation analyses. Results: In total, 145 patients (28 male, 117 female) were included. The PROMs improved significantly across males and females at the latest follow-up. Female patients had significantly lower preoperative PROMs: mHHS (47 vs 57.4; p = 0.002); HOOS pain (44.9 vs 60; p = 0.003), sport (47 vs 57.4; p = 0.002), ADL (58.9 vs 69.3; p = 0.032), and QoL (26.8 vs 39.3; p = 0.009); and UCLA (5.6 vs 6.7, p = 0.042) scores. Males showed higher postoperative UCLA scores (7.5 vs 6.7; p = 0.03). Kendall’s tau showed significant negative correlation between BMI and UCLA scores in females and males (-0.21 to -0.29; p = 0.002/0.048), while BMI and HOOS sport (-0.16; p = 0.015) and ADL (-0.2; p = 0.003), as well as QoL (-0.14; p = 0.031) and preoperative acetabular inclination (-0.13; p = 0.049) were only significantly negatively correlated in females. Conclusion: Patient sex affects PROMs before and after PAO. Female patients experience higher improvement in hip function and activity level, due to poorer preoperative PROMs than males. Thus, these data are particularly interesting in providing preoperative guidance regarding postoperative outcome expectations. Cite this article: Bone Jt Open 2024;6(1):35–42.